Bringing the Congregations Back in: Religious Markets, Congregational Density, and American Religious Participation - Troy Blanchard; Samuel Stroope; Charles Tolbert (Religions, 2014)
We draw on the organizational ecology tradition to frame the relationship between the religious environment of a community and local religious participation. Prior research linking religious environments to religious participation downplays a key organizational aspect of religion: the congregation. Following the organizational ecology usage of density, we argue that congregational density—the number of congregations per person within a community—impacts religious involvement by providing opportunities for participation and by fostering social accountability networks within congregations. Drawing on data from the 2000 Social Capital Community Benchmark Survey, we test the hypothesis that congregational density in a locality is associated with greater religious participation by residents. Our findings indicate that persons residing in congregationally dense communities are more likely to be members of churches, to attend church regularly, to participate in church-based activities, to participate in non-church religious organizations, to volunteer for religious work, and to give to religious causes. These findings hold while controlling for an array of individual and contextual-level variables. This notion of congregational density suggests that local factors transcend broader theological and/or denominational boundaries, resulting in variations in religious participation and commitment.